Citizen Oversight of Public Spaces: Evaluating Public Participation in Managing Privately Owned Public Spaces - Jung, Sungju; Lee, Jae Seung; Kim, Saehoon (Urban affairs review (Thousand Oaks, Calif.), 2025)
Privately owned public spaces (POPS) are intended for public use but are owned and maintained by building owners. Many POPS in Seoul fail to offer a welcoming environment due to inadequate maintenance and illegal private use. In this study, we explored whether citizen participation can effectively enhance the management of POPS and reinforce the general public’s determination to reform public spaces. We involved nonprofessional citizens and local architects in simulated inspections and qualitative assessments of Seoul’s POPS. The citizens were able to effectively identify violations in POPS and provide more rigorous qualitative evaluations from a user perspective than experts. Following the inspection, the citizens developed a new sense of responsibility as stakeholders in urban public spaces. These findings reveal that citizen participation could make POPS more public and empower citizens to become active agents in improving public spaces.